Adoption, continued, and extended use of radio frequency identification (RFID) technology : Australian Livestock Industry - Mohammad Alamgir, Hossain (Curtin University, 2012)
In general, the adoption and diffusion of Information Systems (IS) in agriculture industry is a neglected issue in academia, let alone the livestock sector. In livestock industry, Radio Frequency Identification (RFID) technology is currently used in order to ensure meat safety. Generally, the livestock supply chain involves a large number of people and organisations/farms. To ensure a successful animal-tracing system, the examination of the adoption behaviour of those stakeholders is worthwhile. So far, no initiative has been made by the researchers to investigate the adoption process and relevant factors in a livestock setting. This research aims to close this research-gap. Furthermore, the ultimate success of an innovation is dependent not just on the adoption but on its continued and extended use. Scholars have been investigating on adoption and continuance behaviour of an innovation but not in an integrated fashion.This current research has studied both the adoption and continued and extended usage behaviour of Australian livestock industry regarding RFID technology in a single framework. Moreover, the extension decision of an innovation is a continuous and complex process. It is not easy for farms to identify a correct extension application from many possibilities. As has not been done yet a Decision Support System (DSS), which is based on Analytical Hierarchy Process (AHP), is developed in this research aiming to aid farms to choose the best extension-project.It is assumed that the adoption factors in a mandatory environment would be different than that of in a voluntary environment. In literature, it is very rare to find a comparative study of the adoption factors of a single innovation in both voluntary and mandatory environments. This research studied the both environments.This research adopted the ‘mixed method’ methodology. Face-to-face direct interview with semi-structured questionnaire has been used for the collection of qualitative data. Data obtained from the field study have been analysed using NVivo software package. On the other hand, Partial Least Square (PLS)-based Structural Equation Modelling (SEM) technique has been used for analysing the quantitative data obtained from a national survey on the variables identified earlier from the qualitative method.The findings of this research confirmed that environmental factors, organisational factors, and technological factors influence the adoption of RFID technology in livestock industry. The continued use and extended use of RFID systems are dependent on satisfaction obtained from using the current system. Moreover, confirmation bridges the adoption and continuance; this is the stage which influences the further-use of an innovation after being adopted.This current research has both theoretical and practical implications. Investigating the adoption factors along with continued and extended use factors in a single framework is a unique initiative by far in literature. This research strengthens the adoption-diffusion research of IS by getting insights from the livestock sector. Using the factors and variables, obtained from the research to develop a practical decision making process (i.e., the DSS) is innovative. As practical implications, governments and other organisations that have the power to make an industry to adopt an innovation should consider the findings of this study for efficient policy development and implementation. Similarly, the innovation-vendors/manufacturers may look at the derived factors for a successful acceptance of an innovation. Finally, the DSS does have the merit to be made more extensive and used at farm level in order to assist the farm decision-makers to choose their extension projects.